2018
DOI: 10.1088/1361-6463/aa9f69
|View full text |Cite
|
Sign up to set email alerts
|

Structural, microstructural and electrochemical properties of dispersed-type polymer nanocomposite films

Abstract: The free standing solid polymer nanocomposite (PEO-PVC)+LiPF6-TiO2 films has been prepared through standard solution cast technique. The improvement in structural, microstructural and electrochemical properties has been observed on the dispersion of nanofiller in polymer salt complex. X-Ray diffraction studies clearly reflect the formation of complex formation as no corresponding salt peak appeared in the diffractograms. The FTIR analysis suggested a clear and convincing evidence of polymer-ion, ion-ion and po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 92 publications
2
31
0
Order By: Relevance
“…The almost same trend is followed by the peak associated with melting temperature (Tm) where polymer gets melted. The shift of peak toward lower temperature indicates the increased ionic conductivity and both Tg & Tm supports this approach [83][84]. The crystallinity was calculated using equation 3 and it shows the crystallinity minima for the SPE 2 system.…”
Section: Differential Scanning Calorimetric (Dsc) Analysismentioning
confidence: 75%
“…The almost same trend is followed by the peak associated with melting temperature (Tm) where polymer gets melted. The shift of peak toward lower temperature indicates the increased ionic conductivity and both Tg & Tm supports this approach [83][84]. The crystallinity was calculated using equation 3 and it shows the crystallinity minima for the SPE 2 system.…”
Section: Differential Scanning Calorimetric (Dsc) Analysismentioning
confidence: 75%
“…It is observed that for all SPEs, the initial current decreases with time and achieved steady state in small time. The initial current is the contribution of both the ions and the electrons ( = + ) while the later one is the contribution of electrons only because of blockage of ions at the electrode-electrolyte interface [45][46][47]. The obtained ion transference number is 0.99 (close to unity).…”
Section: Transference Numbermentioning
confidence: 74%
“…However, SPE possesses lower ionic conductivity at ambient temperature. To overcome the poor ionic conductivity various approaches are manifested to develop new materials such as polymer blending, nanofiller dispersion, incorporation of ionic liquids/plasticizer [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of PVB can be demonstrated by the FTIR measurements . As shown in Figure a, the peak at 1666 cm −1 in the spectrum of mPVB membrane is ascribed to the CO stretching vibration of units II and III.…”
Section: Resultsmentioning
confidence: 91%
“…The modification of PVB can be demonstrated by the FTIR measurements. [21][22][23] As shown in Figure 3a, the peak at 1666 cm −1 in the spectrum of mPVB membrane is ascribed to the CO stretching vibration of units II and III. The shift could be contributed to its overlap with the blending vibration peaks of the residual crystal water from the reaction procedures, which are not found in the FTIR spectrum of the PVB membrane.…”
Section: Reaction Mechanismmentioning
confidence: 91%